2023
DOI: 10.1088/1361-6595/ace129
|View full text |Cite
|
Sign up to set email alerts
|

Recombination of oxygen atoms on the surface of oxidized polycrystalline nickel—temperature and pressure dependences

Abstract: The recombination of neutral oxygen atoms in the ground state on the oxidized nickel samples was studied experimentally in the range of pressures where the maximum density occurs in weakly ionized lowpressure oxygen plasma, i.e., between 40 and 200 Pa. The recombination coefficient was determined in the flowing afterglow. The source of oxygen atoms was plasma sustained in a quartz tube of inner diameter 4.7 mm by a microwave discharge in the surfatron mode. The recombination coefficient was determined in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Still, some recent studies reported that the atom loss coefficient for some materials decreases with increasing pressure [49][50][51]. The pressure dependence of the atom loss coefficient for oxygen atoms on nickel and cobalt was studied systematically previously, and the results were published recently [52,53]. Still, any differences between the effects of the mean free path and the pressure dependence of the atom loss coefficient are impossible to distinguish from the results summarized in table 4.…”
Section: Resultsmentioning
confidence: 96%
“…Still, some recent studies reported that the atom loss coefficient for some materials decreases with increasing pressure [49][50][51]. The pressure dependence of the atom loss coefficient for oxygen atoms on nickel and cobalt was studied systematically previously, and the results were published recently [52,53]. Still, any differences between the effects of the mean free path and the pressure dependence of the atom loss coefficient are impossible to distinguish from the results summarized in table 4.…”
Section: Resultsmentioning
confidence: 96%
“…The accuracy of the method is about 20%. Details regarding this method are disclosed in our recent paper [35].…”
Section: Methodsmentioning
confidence: 99%